An Empirical Study of Economic Indicators Impacting GDP of Bangladesh - A Panel Data Analysis - Arvinder Kaur (UIN Mataram, 2021)
Bangladesh is witnessing unprecedented growth in last decade. It is considered the 7th fastest-growing economy globally in the first quarter of 2019, with a rate of 8.3% year-over-year growth.World Bank economists increased the growth projection for Bangladesh this fiscal year by two percentage points, moving the country up to second placein South Asia and the Maldives, where the country is second only to Sri Lanka.According tothe government's most recent projections, Bangladesh's GDP is expected to grow by 5.1% in the fiscal year beginning in July. This research aims to assess the influence of economic indicators on economic growth & the relationship between various indicators impacting economic development. In addition, the study will provide the policymakers an assessment of the right set of practices for economic growth. The analysis is conducted based on panel data for a period ranging from 1986 to 2019 extracted from the World Bank. This study includes statistical data on GDP, gross capital formation, export, foreign direct investment of Bangladesh. Regression and ANOVA techniques are applied to evaluate which indicators have a significant impact on GDP. According to the study, gross capital formation is highly impactful variable whereas export is contributing also towards the growth of GDP but foreign direct investment is considered as insignificant indicator influencing GDP.